Effect of Information Technology and E-Commerce on The Quality of Accounting Information Systems - Yeni Anggraini; Lesi Hertati; Vhika Meiriasari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study ams to determine the effect of information technology and e-commerce on the quality of accounting information systems for gofood traders in the jakabaring sub-district. The Selected sample is 70 respondents using non-probabilitymsampling method. The data for this study were obatained from a questionnaire (primary). The analiysis technique used in this research is descriptive statistical test, data quality test, classical assumption test, multiple linier regression test, and hypothesis test. The results of data analysis with SPSS 26 show that the results of the simultaneous hypothesis test (F-test) based on the value of the coefficient of determination or Adjusted R Aquare (R2) of 0.396 or 39% prove that the variables of information technology and e-commerce together have a positive and significant effect on the quality of accounting information systems Information technology (X1) and e-commerce (X2) and partial hypothesis test results (t-test) Information technology (X1) and e-commerce (X2) affect the quality of accounting information systems (Y).